2017
DOI: 10.1139/cjpp-2016-0418
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of HCN channels in the sinoatrial node of streptozotocin-induced diabetic rats

Abstract: Diabetes mellitus (DM) is associated with an electrical remodeling of the heart, increasing the risk of arrhythmias. However, knowledge of electrical remodeling in the sinoatrial node (SAN) by DM is limited. We investigated the expression of HCN channel isoforms, HCN1-HCN4, in SAN from streptozotocin (STZ)-induced diabetic rats and the age-matched controls. We found that the STZ-induced diabetic rats have a lower intrinsic heart rate, a lengthened sinoatrial conduction time, and rate-corrected maximal sinoatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 51 publications
1
17
1
3
Order By: Relevance
“…This study has shown downregulation of key ion channels proteins important for healthy functioning of the CCS. Previous research has shown significant downregulation of HCN4 in the SAN of STZ rat heart (Huang et al, 2017). Our study has also demonstrated that HCN4 is downregulated in the SAN in the STZ rat compared to controls.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This study has shown downregulation of key ion channels proteins important for healthy functioning of the CCS. Previous research has shown significant downregulation of HCN4 in the SAN of STZ rat heart (Huang et al, 2017). Our study has also demonstrated that HCN4 is downregulated in the SAN in the STZ rat compared to controls.…”
Section: Discussionmentioning
confidence: 80%
“…Cardiac remodeling and altered expression of ion channels may be involved in setting the cardiac rate and rhythm (Movahed, 2007). We have previously shown that TIDM affects a range of mRNA expression in the diabetic SAN (NCX1, Cx45, Ca v 3.1, and HCN4) (Ferdous et al, 2016; Huang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Streptozotocin (STZ)-induced diabetic rats have a lower intrinsic heart rate, an inferior leading pacemaker site, reduced sinoatrial node (SAN) conduction velocity and diastolic depolarization slope, and a longer action potential duration than in the control. The transcripts and proteins of HCN2 and HCN4 in diabetic SAN are reduced, suggesting possible involvement of HCN channels in diabetes-related cardiac problems 91 . In diabetes, bladder Cajal-like interstitial cells are impaired and recently, HCN channels expression associated with caveolae and caveolin was found to be decreased too, suggesting this as one of the molecular mechanisms underlying diabetic bladder problems 92 .…”
Section: Recent Studies and Future Directionsmentioning
confidence: 99%
“…Interestingly, although clinical studies reported efficacy and safety of ivabradine in diabetic patients [21], cardiac effects of ivabradine have been reported to be weaker in rats with streptozotocin (STZ)-induced diabetic heart damage [22]. Recently, reduced expression of HCN channels in the sinoatrial node of streptozotocin (STZ)-induced diabetic rats was found [20]. Therefore, we hypothesize that altered cardiac electrogenesis in diabetes might be affected by changes in cardiac HCN channel expression.…”
mentioning
confidence: 98%
“…Furthermore, I f augmentation induces a diastolic influx of Na + cations leading to increased intracellular Ca 2+ due to the Na + / Ca 2+ exchanger shift towards 'reverse mode' resulting in increased arrhythmogenicity [16]. The overexpression of myocardial HCN occurs in various conditions, including cardiac hypertrophy [17], acute myocardial infarction [18] and heart failure [15] while the reduction of myocardial HCN is rather related to atria and to impaired sinus rhythm [19,20].…”
mentioning
confidence: 99%